Alternative Pathways of Acetogenic Ethanol and Methanol Degradation in the Thermophilic Anaerobe Thermacetogenium phaeum - Keller, Anja; Schink, Bernhard; Müller, Nicolai (Frontiers in Microbiology, 2019)
Abstract Growth of the anaerobic thermophile Thermacetogenium phaeum with methanol, ethanol, ethanolamine, and acetate was investigated in axenic cultures and in syntrophic cultures with Methanothermobacter thermautotrophicus. Microcompartment genes were identified in the T. phaeum genome, and presence of microcompartments was confirmed by transmission electron microscopy and proteome analysis. These genes were expressed only during growth with ethanolamine. Proteome data were compared after growth with all four substrates, and activities of key enzymes of the Wood-Ljungdahl pathway and of enzyme systems leading to production or degradation of acetaldehyde such as alcohol dehydrogenase, aldehyde:ferredoxin oxidoreductase, acetate kinase, and phosphate acetyltransferase were measured in cytoplasmic fractions. Accounting of fermentation stoichiometries and growth yields with all four substrates showed that ethanol and methanol oxidation follow the same stoichiometries as in A. woodii. On the other hand, the pathways of ethanol and methanol degradations vary between both organisms. Growth yields of T. phaeum were substantially lower than reported for A. woodii. Since T. phaeum has no Rnf complex encoded in its genome the mechanisms of ATP synthesis have to be different from those of A. woodii. In addition to the central degradation pathways also found in A. woodii, T. phaeum maintains enzyme systems that compensate for the absence of an Rnf-complex but which on the other hand cause a loss of energy. On the basis of our data, pathways of methanol and ethanol degradation in T. phaeum are discussed.